HUBUNGAN PIJAT BAYI DENGAN FREKUENSI MENYUSU PADA BAYI USIA 1 – 6 BULAN - Suhartik, Suhartik; Kusumawati, Endah (Biomed Science, 2022)
Babby massage is an art of health care that is proven to have many benefits, one of which is that regular massage can improve body health vagus nerovus tone where this process causes increasesd levels of gastrin and insulin absoption enzymes so that absorption of food is better and babies feel hungry faster and often suckle.This research design use correlation analityc method wich cross sectional approach. Population and sample are mothers breastfeeding infants aged 1-6 months. Sampling technicque using non-probability sampling with purposive sampling. The number of samples as many as 30 respondents. Data collection of independent (baby massage) and dependent variables (suckle frequency) using a questionnaire. Data processingby editing, coding, scoring, tabulating, data analysis using chi square using SPSS software 16.00The result of the study showed that more then some mothers breastfeed their babies at BPM M. Susyati TAR, Amd. Keb., S. Pdas many as 23 respondents (76,7%) with most of them having frequent feedings. While mothers who do not regulary massage their babies as many as 7 respondent (23,3%) have less frequency of breastfeeding as many as 5 respondent (16,7%). So there is a relationship between baby massage and breastfeeding frequency with a significant value of 0,0001, so the hypothesis is accepted.The conclusion of this study is that there is a relationship between baby massage and the frequency of breastfeeding in infants aged 1-6 months at BPM M. Susyati TAR, Amd Keb. S.Pd desa Ledokwetan Kecamatan Bojonegoro Kabupaten Bojonegoro. Introduction, counseling and training to health works or infant mothers on infant massage can improve the implementationof infant massage so that it can help improve the growth and development program for infant and toddlers.